DETERMINAN RENDAHNYA PEMAHMAN MASYARAKAT, PERSEPSI DAN SOSIALISASI TERHADAP BANK SYARIAH INDONESIA DI SULAWESI SELATAN - Ibrahim Ibrahim; Abdul Khalik; Taufik Thahir; Erik Rachim (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
This study aims to determine and analyze the partial influence of public understanding, public perception and level of socialization about the operational system of Indonesian Islamic banks in South Sulawesi and to determine and analyze the simultaneous influence of public understanding, public perception and level of socialization of the operational system of Indonesian Islamic banks in Makassar. and the variables that have the dominant influence of the three variables studied on Indonesian Sharia Banks in South Sulawesi Based on the results of the t test (partial test) it shows that Community Understanding, Community Perception and Socialization have a positive and significant effect on Indonesian Sharia Banks in South Sulawesi. Meanwhile, the results of the simultaneous test (Test F), show Community Understanding, Community Perception and Socialization have a positive and significant effect on Indonesian Sharia Banks in South Sulawesi. The variable that has the dominant influence on Makassar Indonesian Sharia is the Community Understanding variable with a